Aqp9 mediates lactate transport in human placenta as an alternative energy substrate - Medina Mora, Yollyseth Astrid (2020)
Emerging evidence shows that placental aquaporin-9 (AQP9) is notinvolved in the transfer of water between the mother and the fetus.However, its role in human placenta is still unknown. AQP9 is anaquaglyceroporin that also permeates other solutes such as lactate. Inbrain, AQP9 may transport lactate as an alternative energy substrate.OBJECTIVE: Our aim was to evaluate the participation of AQP9 inthe lactate transfer across the human placenta.METHODS: This study was approved by the ethics committee of theHospital Nacional Dr. Prof. A. Posadas. Explants from normal termplacentas were cultured in low glucose with or without L-lactate, andin presence and absence of AQP9 inhibitors (0.3 mM HgCl2, a general blocker of AQPs, or 0.5mM Phloretin, to block AQP9). Normalglucose medium was used as control. Cell viability was assessed byMTT assay and LDH release. Apoptosis indexes were analyzed byBax/Bcl-2 protein expression ratio and TUNEL assay.RESULTS: In low glucose medium, MTT decreased while LDHrelease did not change compared to controls, suggesting that celldeath is not due to necrosis. Moreover, Bax/Bcl-2 ratio and apoptoticnuclei increased (n=5, p <0.02) and the blocking of AQP9 did notabrogate apoptosis. However, when explants were cultured in lowglucose medium supplemented with L-lactate, explant viability andapoptotic indexes were similar to controls indicating that L-lactatecould be replacing glucose as an energy substrate. In this case, theblocking of AQP9 resulted in an increase in cell death (n=4, p <0.05),proposing that this protein has a role in lactate transport.CONCLUSION: Our results show that placental AQP9 may havea key role in lactate transport as an alternative energy substrate.Thus, the blocking of lactate transport mediated by AQP9 negativelyaffects the survival of trophoblast cells.